Ionic mass transfer at rotating electrodes formed by solids of revolution : Rotating one-base spherical segment electrodes - Cobo, O. A. (1972)
The ionic mass transfer at rotating electrodes formed by a one-base spherical segment has been experimentally studied by the usual electrochemical methods. For electrodes which involve an electrochemical active area having angle up to 40 deg, the mass-transfer rate equation is [fórmula en el documento].